Responses of metastatic basal cell and cutaneous squamous cell carcinomas to anti-PD1 monoclonal antibody REGN2810. Issue 1 (15th November 2016) - Falchook, Gerald S.; Leidner, Rom; Stankevich, Elizabeth; Piening, Brian; Bifulco, Carlo; Lowy, Israel; Fury, Matthew G.
Abstract : Background: Basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (CSCC) share exposure to UV light as the dominant risk factor, and these tumors therefore harbor high mutation burdens. In other malignancies, high mutation burden has been associated with clinical benefit from therapy with antibodies directed against the Programmed Death 1 (PD-1) immune checkpoint receptor. Highly mutated tumors are more likely to express immunogenic tumor neoantigens that attract effector T cells, which can be unleashed by blockade of the PD-1 immune checkpoint. Case presentations: This report describes a patient with metastatic BCC and a patient with metastatic CSCC who were treated with REGN2810, a fully human anti-PD-1 monoclonal antibody, in an ongoing phase 1 trial (NCT02383212 ). The CSCC patient has experienced an ongoing complete response (16+ months), and the BCC patient has experienced an ongoing partial response (12+ months). Conclusions: These case reports suggest that UV-associated skin cancers, beyond melanoma, are sensitive to PD-1 blockade. Trial registration: Clinicaltrials.gov NCT02383212 . Registered 2 February 2015.